Improvement of hERG-ROMK index of spirocyclic ROMK inhibitors through scaffold optimization and incorporation of novel pharmacophores. Issue 11 (1st June 2017) - Dong, Shuzhi; VanGelder, Kelsey; Shi, Zhi-Cai; Yu, Yang; Wu, Zhicai; Ferguson, Ron; Guo, Zack Zhiqiang; Tang, Haifeng; Frie, Jessica; Fu, Qinghong; Gu, Xin; Priest, Birgit T.; et al.
Graphical abstract: Abstract: SAR in the previously described spirocyclic ROMK inhibitor series was further evolved from lead4 by modification of the spirocyclic core and identification of novel right-side pharmacophores. In this process, it was discovered that the spiropyrrolidinone core with the carbonyl group α to the spirocenter was preferred for potent ROMK activity. Efforts aimed at decreasing hERG affinity within the series led to the discovery of multiple novel right-hand pharmacophores including 3-methoxythiadiazole, 2-methoxypyrimidine, and pyridazinone. The most promising candidate is pyridazinone analog32 that showed an improved functional hERG/ROMK potency ratio and preclinical PK profile. In vivo evaluation of32 demonstrated blood pressure lowering effects in the spontaneously hypertensive rat model.